The new rules of marketing & PR how to use social media, online video, mobile applications, blogs, newsjacking, and viral marketing to reach buyers directly - Scott, David Meerman (John Wiley & Sons, Inc., 2017)
The international bestseller-now in a new edition When it comes to marketing, anything goes in the Digital Age, right' Well, not quite. While marketing and public relations tactics do seem to change overnight, every smart businessperson knows that it takes a lot more than the 'next big thing.' The New Rules of Marketing & PR is an international bestseller with more than 375,000 copies sold in twenty-nine languages. In the latest edition of this pioneering guide to the future of marketing, you'll get a step-by-step action plan for leveraging the power of the latest approaches to generating attention for your idea or your business. You'll learn how get the right information to the right people at the right time-at a fraction of the cost of traditional advertising. The Internet continues to change the way people communicate and interact with each other, and if you're struggling to keep up with what's trending in social media, online videos, apps, blogs, or more, your product or service is bound to get lost in the ether. In The New Rules of Marketing & PR, you'll get access to the tried-and-true rules that will keep you ahead of the curve when using the latest and greatest digital spaces to their fullest PR, marketing, and customer-communications potential. Keeping in mind that your audience is savvy and crunched for time, this essential guide shows you how to cut through the online clutter to ensure that your message gets seen and heard.-Serves as the ideal resource for entrepreneurs, business owners, marketers, PR professionals, and non-profit managers -Offers a wealth of compelling case studies and real-world examples -Includes information on new platforms including Facebook Live and Snapchat -Shows both small and large organizations how to best use Web-based communication Finally, everything you need to speak directly to your audience and establish a personal link with those who make your business work is in one place.
Earlier edition: 2015. - Includes index. - Includes bibliographical references and index. - Online resource; title from PDF title page (EBSCOhost, viewed February 1, 2018)
Keywords: Internet marketing; Internet in public relations; Marketing sur Internet; Internet dans les relations publiques; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior